1998
DOI: 10.1021/np9705468
|View full text |Cite
|
Sign up to set email alerts
|

A Sulfated Saponin from Bupleurum rigidum

Abstract: A new sulfated triterpene glycoside with the sulfate group located in an unusual position in the carbohydrate moiety, was isolated from the MeOH extract of the aerial parts of Bupleurum rigidum. This compound was identified by a combination of chemical degradation and spectral methods as 3beta,16beta,23-trihydroxy-13, 28-epoxyolean-11-en-3beta-yl-beta-D-glucopyranosyl-(1-->2)[4-sulfate- beta-D-glucopyranosyl-(1-->3)]-beta-D-fucopyranoside (sandrosaponin I) (1). In addition, the known compound 3beta,16beta, 23-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…The methanol extract was dried and partitioned between H 2 O and n -butanol, and the butanol extract was subjected to Si gel column chromatography to afford compounds 1 − 4 and a previously known saponin. The 1 H and 13 C NMR spectra of this substance were identical to those published data, and comparison with an authentic sample demonstrated that it was 3β,16β,23-trihydroxy-13,28-epoxyolean-11-en-3β-yl β- d -glucopyranosyl-(1→2)-[β- d -glucopyranosyl-(1→3)]-β- d -fucopyranoside (buddlejasaponin IV). , …”
Section: Resultssupporting
confidence: 76%
“…The methanol extract was dried and partitioned between H 2 O and n -butanol, and the butanol extract was subjected to Si gel column chromatography to afford compounds 1 − 4 and a previously known saponin. The 1 H and 13 C NMR spectra of this substance were identical to those published data, and comparison with an authentic sample demonstrated that it was 3β,16β,23-trihydroxy-13,28-epoxyolean-11-en-3β-yl β- d -glucopyranosyl-(1→2)-[β- d -glucopyranosyl-(1→3)]-β- d -fucopyranoside (buddlejasaponin IV). , …”
Section: Resultssupporting
confidence: 76%
“…The chemical shift of H-4′ (δ H 4.17) was unusually high for glucose, suggesting that the sulfate group was attached at this position. The chemical shift of H-4′ is consistent with literature values. Thus, compound 22 was identified as a new sulfated analogue of ginsenoside Ro ( 21 ).…”
Section: Resultssupporting
confidence: 87%
“…Saikosaponins were isolated from S. scorodonia and B. rigidum, and identified as buddlejasaponin I and IV and sandrosaponin 1 (see Fig. 3 for structures) as described in detail elsewhere [4]. Chromatographic analysis (TLC) and NMR spectra showed the purity of compounds.…”
Section: Chemicalsmentioning
confidence: 99%
“…Many studies have reported on the chemical and pharmacological activities of B. falcatum, whose roots are an officinal drug cited in the Japanese Pharmacopoeia. The active constitu-ents of these drugs have been proved to be saikosaponins, which are oleanane derivatives found in other Bupleurum species, such as in B. gibraltaricum and B. rigidum growing in Spain [3], [4]. Saponins in general are known to have a wide range of biological properties, including antiviral activity [5], [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%